Cooperative learning strategies to develop and assess values and soft skills among technical and vocational students - Khalid, Madihah; Pg Hj Metersad, Dk. Hjh Marlina (2016)
This study investigates the feasibility of utilizing Cooperative Learning as a pedagogy in developing and assessing values and Soft Skills on the Vocational and Technical Institution (VTI) students. In addition, the study also explores the effect of Cooperative learning (in this case Students Teams-Achievement Division (STAD) on students’ achievement and attitude towards learning Mathematics. A total of forty four students and fifty five instructors were involved in this study which collected qualitative and quantitative data via questionnaires, interviews, observations and journals. These various methods of data collection were employed to support and triangulate the study to give a more credible analysis and result. In the first part of the research; from the surveys and interviews conducted, it was found that the majority of the instructors did recognize the potentials of Cooperative Learning in developing as well as assessing of Soft Skills and positive values among VTI students. In addition, Cooperative Learning was seen to possibly provide solutions in enhancing the assessment of Soft Skills. The result also showed significant improvement in VTI students’ learning in terms of achievement and attitude towards Mathematics. However, the need to consider Cooperative Learning as a feasible pedagogy for learning and fostering values will depend on the students’ familiarity with the strategy and their acceptance of it. In conclusion, Cooperative Learning in this study has shown advantageous gains for the VTI students in terms of cognitive thinking and attitude towards learning Mathematics.